Desa Karya Pandhi sebagai Representasi Pandai Besi Tradisional di Paterongan Kecamatan Galis Kabupaten Bangkalan, Jawa Timur - Sari, Yuliana Windi; Prastiwi, Merlia Indah; Effendi, Masitah; Kusumawardhana, Indra Jaya; Biroli, Alfan; Mutmainah, Mutmainah (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2025)
The village of Pandhi's work is a village whose community activities are traditional blacksmith craftsmen in Paterongan Village, Galis District, Bangkalan Regency, traditional blacksmith craftsmen are a form of community economic existence based on the community's ability to process metal and iron traditionally into tools used daily such as clurit, machetes, knives. The sustainability of this blacksmith craft business still requires further development, especially with regard to institutions and skills. The research method used to determine the existence of traditional blacksmith crafts uses qualitative research methods by collecting data by conducting interviews and observations to traditional blacksmith craftsmen. Based on the results of the study, it is known that this traditional blacksmith craft is a hereditary family business, Blacksmiths also work with the concept of full-time and part-time, their social activities as blacksmiths that make them have a “workshop” in each house that is used to process iron into tools that are ready for sale. The existence of this traditional blacksmith craft is not only related to how the community can survive but how socially, economically supported by the existence of this traditional blacksmith craft. Blacksmith crafts included in the informal sector require capacity building from relevant stakeholders such as the local district government so that the characteristics of traditional blacksmith crafts are not eroded by changes and the iron and metal processing industry on a large scale.